2018
DOI: 10.1007/s00464-018-6416-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of metal versus plastic stents for drainage of pancreatic fluid collections: metal stents are advantageous

Abstract: The use of metal stents for drainage of pancreatic fluid collections is associated with improved clinical success, fewer adverse events and reduced bleeding compared to plastic stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…However, previous observations of the two stent types found them comparable without high-quality evidence to favor one over the other [48]. Indeed, meta-analyses on the topic have had variable results with more recent publications favoring metal stents over double pig-tail stents [49,50]. Nonetheless, these studies reported outcomes for PFC in general.…”
Section: Discussionmentioning
confidence: 96%
“…However, previous observations of the two stent types found them comparable without high-quality evidence to favor one over the other [48]. Indeed, meta-analyses on the topic have had variable results with more recent publications favoring metal stents over double pig-tail stents [49,50]. Nonetheless, these studies reported outcomes for PFC in general.…”
Section: Discussionmentioning
confidence: 96%
“…In the recent years, the debate regarding the appropriate stent for EUS‐guided PFC drainage has again come into the spotlight. Several systematic reviews with traditional pairwise meta‐analysis comparing metal and plastic stents in EUS‐guided PFC drainage are available . Although these data showed that metal stents improved clinical outcomes and safety compared with plastic stents, some important questions remained unaddressed, such as which metal stent improves clinical outcomes and safety profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, LAMS designed for the drainage of pancreatic collections have appeared with demonstrated efficacy in a number of studies but they are also more costly [16][17][18][19][20]. These stents are totally covered and offer a maximum caliber of 15-20 mm, thereby allowing for endoscopic necrosectomy in repeated sessions without the need for replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Although some international systematic endoscopic reviews and meta-analysis have recommended LAMS as the care standard for WON drainage, the quality of evidence is not high (retrospective, registry-based, or non-comparative) that LAMS are superior to PLASTIC stents in the management of WON by EUS-guided transmural drainage, and few studies have compared LAMS and plastic stents [15][16][17][18][19][20]. For all these reasons, a multicenter prospective, parallel group, randomized controlled clinical trial was designed to assess whether LAMS are superior to plastic stents in the endoscopic treatment of WON.…”
mentioning
confidence: 99%